2011
DOI: 10.1371/journal.pone.0026386
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Stimulus Salience and Attentional Capture Across the Neural Hierarchy in a Stop-Signal Task

Abstract: Inhibitory motor control is a core function of cognitive control. Evidence from diverse experimental approaches has linked this function to a mostly right-lateralized network of cortical and subcortical areas, wherein a signal from the frontal cortex to the basal ganglia is believed to trigger motor-response cancellation. Recently, however, it has been recognized that in the context of typical motor-control paradigms those processes related to actual response inhibition and those related to the attentional pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 55 publications
8
31
0
Order By: Relevance
“…A smaller cluster was revealed in the rIFJ, a dorsal IFG region extending into the right precentral gyrus ( Figure 3A). These are consistent with previous findings regarding key nodes of the right IFC engaged in inhibitory control performance (Barber, Caffo, Pekar, & Mostofsky, 2013;Boehler et al, 2011;Cai & Leung, 2011;Chikazoe et al, 2009;Hampshire, Thompson, Duncan, & Owen, 2009;Hodgson et al, 2007;Leung & Cai, 2007;Aron, 2006;Li, Huang, Constable, & Sinha, 2006;Kelly et al, 2004;Aron et al, 2003;Menon, Adleman, White, Glover, & Reiss, 2001;Rubia et al, 2001;Garavan et al, 1999;Konishi et al, 1999;Kawashima et al, 1996), as is the right medial pre-SMA, which also yielded a large cluster of activity ( Figure 3B; Chen, Scangos, & Stuphorn, 2010;Sharp et al, 2010;Duann, Ide, Luo, & Li, 2009;Nachev, Kennard, & Husain, 2008;Picton et al, 2007;Sumner et al, 2007;Floden & Stuss, 2006;Li et al, 2006). Consistent with a number of studies (Criaud & Boulinguez, 2013;Hirose et al, 2012;Zhang & Li, 2012;Swick, Ashley, & Turken, 2008;Rubia et al, 2001), successful inhibitory control was associated with left-lateralized activity in a ventral region of the IFG extending into the anterior insula ( Figure 3D).…”
Section: Whole-brain Event-related Activity For Successful No-go Trialssupporting
confidence: 92%
See 1 more Smart Citation
“…A smaller cluster was revealed in the rIFJ, a dorsal IFG region extending into the right precentral gyrus ( Figure 3A). These are consistent with previous findings regarding key nodes of the right IFC engaged in inhibitory control performance (Barber, Caffo, Pekar, & Mostofsky, 2013;Boehler et al, 2011;Cai & Leung, 2011;Chikazoe et al, 2009;Hampshire, Thompson, Duncan, & Owen, 2009;Hodgson et al, 2007;Leung & Cai, 2007;Aron, 2006;Li, Huang, Constable, & Sinha, 2006;Kelly et al, 2004;Aron et al, 2003;Menon, Adleman, White, Glover, & Reiss, 2001;Rubia et al, 2001;Garavan et al, 1999;Konishi et al, 1999;Kawashima et al, 1996), as is the right medial pre-SMA, which also yielded a large cluster of activity ( Figure 3B; Chen, Scangos, & Stuphorn, 2010;Sharp et al, 2010;Duann, Ide, Luo, & Li, 2009;Nachev, Kennard, & Husain, 2008;Picton et al, 2007;Sumner et al, 2007;Floden & Stuss, 2006;Li et al, 2006). Consistent with a number of studies (Criaud & Boulinguez, 2013;Hirose et al, 2012;Zhang & Li, 2012;Swick, Ashley, & Turken, 2008;Rubia et al, 2001), successful inhibitory control was associated with left-lateralized activity in a ventral region of the IFG extending into the anterior insula ( Figure 3D).…”
Section: Whole-brain Event-related Activity For Successful No-go Trialssupporting
confidence: 92%
“…Recent work, however, suggests that variation in inhibitory control performance may not always be exclusively attributable to behavioral stopping processes per se. Variation in performance may instead be mediated by other mechanisms related to processes such as salience, attention, and motivation (Salinas & Stanford, 2013;Wiecki & Frank, 2013;Chatham et al, 2012;Boehler, Appelbaum, Krebs, Chen, & Woldorff, 2011). As a consequence, modulation of DR-IP performance may be more closely associated with other neural nodes in the inhibitory control network, which are implicated in stimulus-driven and goal-directed attention such as the right inferior frontal junction (rIFJ; Corbetta & Shulman, 2011;Asplund, Todd, Snyder, & Marois, 2010;Brass, Derrfuss, Forstmann, & Cramon, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There is broad evidence in the literature that the rIFC, especially the posterior part of the rIFC, plays a pivotal role in response inhibition (Aron, 2011;Aron and Poldrack, 2006;Chambers et al, 2006Chambers et al, , 2007Chevrier et al, 2007;Chikazoe et al, 2009;Garavan et al, 1999;Rubia et al, 2003;Swann et al, 2012). Yet, it might also be involved in attentional processing of a stop-signal (Boehler et al, 2011;Dodds et al, 2011;Hampshire et al, 2010;Sharp et al, 2010). Some authors have, thus, argued that the pre-SMA rather than the rIFC might be critical for response inhibition (Chao et al, 2009;Duann et al, 2009;Floden and Stuss, 2006;Li et al, 2006;Sharp et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Participants could, therefore, predict the occurrence of the distracting item and this may have strengthened the involvement of inferior frontal gyrus in actively monitoring the distractors. Kobayashi et al [48] reported that while occipital areas were mostly blind to the task relevance of stimuli, activity profiles in frontal areas depended on task relevance, presumably reflecting a combination of top-down attentional influences and inhibitory motor-control processes (see also [49] for a similar account).…”
Section: Discussionmentioning
confidence: 99%
“…Based on neuroimaging data, Boehler et al [49] suggested that the area that appeared to be most consistently activated by the rarity and salience of stimuli, irrespective of task relevance, is the bilateral intra-parietal lobule. Anderson and Rees [18] found that a salient cue elicited attentional capture and an increase in BOLD signal in the SC of human subjects.…”
Section: Discussionmentioning
confidence: 99%